Profile Variables as a Basis for Segmenting Markets: A Guesthouse Perspective - Amoah, Felix; Radder, Laetitia; van EykMarlé (Journal of Economics and Behavioral Studies, 2018)
Marketers frequently use profile variables to differentiate between groups of customers. The question arises as to whether these variables can also be used by guesthouses in segmenting their market. Segmentation helps marketers better meet customers’ needs and leads to increased customer satisfaction. This study determines whether significant differences exist in visitors’ perceptions of experience realms, given their age, gender, education level, and prior visits to the guesthouse, and whether these variables can be used in segmenting the market. The analysis of data provided by 541 guests who stayed at 51 guesthouses in Ghana shows that visitors from different age groups differ significantly with respect to the experience realms, except for Escape. Prior visits to the guesthouse resulted in significant differences in perceptions of Entertainment, Escape, Atmospherics, Peace of mind, and Efficiency, while education resulted in different perceptions of the Entertainment realm . The results can assist guesthouse managers in Ghana in allocating resources to segments that would yield maximum returns in Ghana.